(untitled) (International relations and international law Journal, 2023)
Numerous Central Asian transport projects supported by global powers like the USA, EU, and China aim to establish alternative routes bypassing Russia. These corridors include North-South, trans-Iranian, and proposed routes connecting various regions. Kazakhstan should view these developments as opportunities and focus on providing reliable, cost-effective logistics solutions. Kazakhstan faces competition from Russian and Belarusian road transport services and sea transport options. The Europe-Kazakhstan-China railway offers economic advantages due to shorter distances and higher speed. This study examines the logistical and geopolitical aspects of international transport corridors in Kazakhstan, emphasizing modern challenges and Kazakhstan’s competitiveness. It explores how Kazakhstan leverages its strategic location amid global efforts to create overland transport corridors. As China seeks alternative sea routes via the Suez Canal, Kazakhstan can serve as a crucial trade bridge between East and West. The research adopts a geopolitical perspective, recognizing the influence of transport and logistics on modern political dynamics. It aims to comprehensively analyze elements shaping Kazakhstan’s transport policy and its role in the global transport network. Keywords: Kazakhstan, Transport, Transit, Logistics, Road, Central Asia.